Utilizing mast cells in a positive manner to overcome inflammatory and allergic diseases - Zhang, Zhongwei; Ernst, Peter B.; Kiyono, Hiroshi; Kurashima, Yosuke (Frontiers in Immunology, 2022)
Mast cells (MCs) are immune cells that are widely distributed in the body, accompanied by diverse phenotypes and functions. Committed mast cell precursors (MCPs) leave the bone marrow and enter the blood circulation, homing to peripheral sites under the control of various molecules from different microenvironments, where they eventually differentiate and mature. The high functional heterogeneity of MCs is partly attributable to their unique maturation mechanisms. High plasticity also means that MCs can exhibit different subtypes to cope with different microenvironments, called the peripheral immune education system. It is generally known that MCs exacerbate allergic and inflammatory reactions; however, recently accumulated evidence also reveals that MCs inhibit these pathological reactions in some cases. In this review, we focus on the mucosal tissues, such as the gastrointestinal tract, to gain insights into mechanism underlying the migration of MCs to the gut and their heterogeneity, which is driven by different microenvironments. In particular, the immunosuppressive properties of MC let us consider that bringing MCs over to our side is a way to overcome inflammatory and allergic disorders.